Obesity in childhood: associations with parental neglect, nutritional habits, and obesity awareness - Onay, Tuba; Beyazıt, Utku; Uçar, Aslı; Bütün Ayhan, Aynur (Frontiers in Nutrition, 2024)
Background: The relationships underlying the dynamic between obesity and parental neglect in terms of nutritional habits and obesity awareness are unclear. Parental neglect remains a significant subject of concern that needs to be examined in the context of obesity. Methods: The aim was to examine the relationships between childhood obesity, parental neglect, children's eating habits and obesity. The study group consisted of 404 children and their parents from Ankara, Turkiye. As data collection tools, an Individual Information Form, Obesity Awareness Scale, the Parents Form of the Multidimensional Neglectful Behaviors Scale were administered. In addition, information on the children's body mass indexes was obtained by anthropometric measurements and the findings were recorded on the questionnaires of each child. Results: It was found that 98 (24.3%) of the children included in the study were overweight and 63 (15.6%) were obese. The results of the multinomial logistic regression analysis indicated that in the underweight and overweight group, the parents' perception of their child's weight predicted body mass index in children, and in the obese group, along with the parents' perception of their child's weight, the age and gender of the child, eating fast, obesity in the family and parental neglect were also predictors. Conclusions: Practitioners such as nurses, dietitians and child developmentalists working in schools should consider weight problems in children as one of the indicators of parental neglect and should implement interventive efforts to enhance parental supervision of children at risk.